Determinan Kualitas Hasil Audit Aparat Inspektorat dalam Keuangan Daerah Provinsi Nusa Tenggara Barat - Defel Septian; R . Ayu Ida Aryani; Muliani Muliani (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
This study used 20 internal auditors of West Nusa Tenggara Inspectorate Apparatus as sample, determined based on saturated or census sampling method. This study uses multiple linear regression analysis with the quality of local government internal audit results as the dependent variable as well as the independence, integrity and competence of internal auditors as independent variables. The results of this study indicate that there is positive and partial influence between the independence and auditor integrity to the audit quality. Meanwhile, the study found that competence has no positive and significant influence on the quality of audit result. The coefficient of determination indicates that the independent, integrity and competence simultaneously affect the dependent variable (the quality of audit result) of 41,5%, while the remaining 58,5% influenced by other factors.